Peer attachment with emotion regulation: The influence of affective and cognitive empathy as moderators - Siti Muntamah, Bening; Fikri Pratama, Muhammad (Psikologia: Jurnal Pemikiran dan Penelitian Psikologi, 2025)
This research examines the role of affective and cognitive empathy as moderators in the relationship between peer attachment and cognitive reappraisal and expressive suppression of emotion regulation in adolescents. The research used a quantitative survey design with 96 junior high school students as participants. Peer attachment was measured using the peer attachment subscale of the Inventory of Parent and Peer Attachment (IPPA), affective and cognitive empathy were measured using the affective and cognitive empathy subscales of the Adolescent Measure of Empathy and Sympathy (AMES), and cognitive reappraisal and expressive suppression of emotion regulation were measured using the Emotion Regulation Questionnaire for Children and Adolescents (ERQ-CA). The results showed a positive relationship between peer attachment and cognitive reappraisal, affective and cognitive empathy with cognitive appraisal. The study also found that affective empathy can mediate the relationship between peer attachment and cognitive reappraisal. This suggests that adolescents’ stronger peer attachment and higher levels of affective empathy are associated with a better ability to use cognitive reappraisal to regulate their negative emotions. However, no significant relationships were found between peer attachment, affective empathy, and cognitive empathy with expressive suppression. This may be because other factors influence expressive suppression. These findings highlight the importance of understanding the role of empathy in helping adolescents manage negative emotions through cognitive reappraisal. The implications of this study can support the development of more effective interventions to help adolescents better manage their emotions.